2018
DOI: 10.3390/ma11071132
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Dissimilar Friction Stir Welded between the Al–Li–Cu and the Al–Zn–Mg–Cu Alloys

Abstract: In this paper, the microstructure of friction stir welded between the Al–Li–Cu alloy and the Al–Zn–Mg–Cu alloy was studied using optical microscope(OM), electronic backscattered diffraction (EBSD), SEM, and TEM. The hardness profile revealed that the range of heat affect zone for the Al–Zn–Mg–Cu alloy was slightly wider than the Al–Li–Cu alloy when they suffered from the thermal transient. Additionally, the characterization of precipitates inside the different zones was obviously different, which corresponded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Martinez et al [47] reported that the dissolution and coarsening of both metastable η' precipitates and stable η precipitates are affected by both the peak temperature and the duration of time at elevated temperatures. Consequently, the dwell time and the peak temperature in HAZ have a significant impact on the dissolution or coarsening of η' precipitates [45,47,48]. As a result, the travel speeds give rise to different features of precipitation.…”
Section: Microstructures Of Hazmentioning
confidence: 99%
“…Martinez et al [47] reported that the dissolution and coarsening of both metastable η' precipitates and stable η precipitates are affected by both the peak temperature and the duration of time at elevated temperatures. Consequently, the dwell time and the peak temperature in HAZ have a significant impact on the dissolution or coarsening of η' precipitates [45,47,48]. As a result, the travel speeds give rise to different features of precipitation.…”
Section: Microstructures Of Hazmentioning
confidence: 99%
“…Son yıllarda magnezyum, titanyum, bakır [3][4][5], düşük karbonlu çelikler, paslanmaz çelikler, pirinçler, kompozitler ve termoplastik malzemelerin [6][7][8][9][10] birleştirilmesinde kullanılmaktadır. Son zamanlarda, alüminyum-çelik, alüminyum-magnezyum, alüminyumun-bakır, alüminyumun-gümüş ve magnezyum-çelik gibi farklı metallerinkaynağında da bu kaynak tekniği kullanılmaya başlanmıştır [11][12][13].…”
Section: Introductionunclassified
“…The research emphasis at present relating to Al/Mg FSW joints with interlayers is focused on the enhancement of the mechanical properties. In addition to the mechanical properties, corrosion properties are another key issue for joint safety in the service course [13,14]. In general, preferential corrosion occurs at the Mg alloy in Al/Mg FSW joints because of its lower corrosion potential, which will damage the joint strength and lead to joint failure, compared with that of the Al alloy [15,16].…”
Section: Introductionmentioning
confidence: 99%